PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS RME UNTUK MAHASISWA PGMI DI IAIN CURUP - Dini Palupi Putri (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2019)
This Development Research develops teaching materials based on Realistic Mathematic Education for third semester students in the SD / MI Mathematics subject of the Madrasah Ibtidaiyah Teacher Education Study Program. The purpose of mathematics learning is for students to be proficient in mathematical abilities, to support it, it needs good media, one of the teaching materials. Students 'perceptions of teaching materials used so far have not led to the development of students' mathematical abilities. Students assess teaching material does not yet contain the learning context to build initial knowledge and relate material to day-to-day experiences. For that lecturers and students need teaching materials that are easy, practical and efficient to develop mathematical abilities. RME is an approach whose activities further emphasize the context and interactivity of students in developing mathematical abilities. The concepts contained in teaching materials are related to the experiences of everyday life. Teaching materials developed based on the results of perceptions and needs of lecturers and students, then validated by experts, then revisions based on suggestions from the validator.